CRITICAL DIMENSIONS OF WELL-BEING IN SELANGOR, MALAYSIA - Husin, Nor Azilah; Ngah, Fahmi; Yulia, Astri; Azim, Zainal Azhar Zainal; Ghazali, Amirul Syafiq Mohd (Indian Journal of Finance and Banking, 2020)
Selangor is leading the other thirteen states in Malaysia in the economy, making it one of the most preferred places to stay for its economic flourish, employment prospect, great infrastructure, and excellent facilities. Selangor is ranked the highest by contributing 23% of its National Gross National Product to Malaysia. Nevertheless, for social indicators, Selangor ranked fourth in the country. Social development was not at par with the fast-growing economy and the extensive physical developments that take place. Thus, the objective of this paper is to identify the critical dimensions of Selangorians’ well-being. We adapted a questionnaire from a Gallup survey and distributed it about 1500 questionnaires to people in Selangor using random and non-proportionate stratified sampling in twelve (12) municipalities of the state. We employed SPSS 22.0 for descriptive results and Smart PLS 3.0 for the structural equation modeling. The finding revealed that the economic dimension (t-values =5.141), environment dimension (t-values =6.668), health dimension (t-value=5.092), and spiritual dimension (t-values= 4.969) were significant to well-being except for emotion dimension (t-values =0.283). This finding provides insights to practitioners, local authorities, and policymakers of the state government in enhancing Selangorians’ quality of life and well-being. JEL Classification Codes: I31, I38.